A Multi-Objective Approach for Voltage Stability Enhancement and Loss Reduction under PQV and P Buses Through Reconfiguration and Distributed Generation Allocation - Barnwal, Akhilesh Kumar; Yadav, Lokesh Kumar; Verma, Mitresh Kumar (Institute of Electrical and Electronics Engineers Inc., 2022)
This paper proposes a novel approach of voltage stability enhancement and power loss minimization in addition to maintenance of good voltage profile in radial distribution networks through optimally placed distributed generation, network reconfiguration and voltage control of PQV bus through variable reactive power source at P bus. A multi-objective function has been proposed that considers maximum system loadability enhancement and network loss minimization. Optimization of proposed multi-objective function, under distributed generation and network reconfiguration with presence of PQV and P buses in the system have been done using grey wolf optimization technique. Case studies performed on IEEE 33-bus radial distribution system shows that presence of PQV and P buses in the system yields significant enhancement in voltage stability margin under optimal placement of distributed generations and network reconfiguration.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Distributed generation; Grey wolf optimization; PQV and P buses; Reconfiguration; Distributed power generation; Reactive power; Voltage control; Networks reconfiguration; Power systems stability; Stability criterions; Stability criteria